Linking eating and weight control attitudes to relationship experiences: A large-scale survey of adolescent females. (July 2017) - Thomas, Rebekah L.; Kelly, Adrian B.; Chan, Gary C.K.; Williams, Joanne W.
Abstract: Objective: To examine the extent to which family conflict, peer bullying and psychological distress account for eating and weight loss attitudes in adolescent females. This study examined the degree to which psychological distress mediated the association between family conflict and eating and weight loss attitudes, and the association of bullying and eating and weight loss attitudes. Method: Females aged between 11 and 17 years ( N  = 5125) were recruited from schools in the State of Victoria (Australia). Key measures included psychological distress, family conflict, and bullying victimisation. Results: A structural model showed good fit, and all predictors were significant. Psychological distress mediated the association between eating and weight loss attitudes, and family problems and bullying. Conclusion: Family conflict and peer bullying were associated with eating and weight loss attitudes and this association may occur via psychological distress. Early intervention programs may benefit from a focus on family and peer relationships.